2010
DOI: 10.1677/jme-09-0166
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol down-regulates lipopolysaccharide-induced MCP-1 production and cell migration in vascular smooth muscle cells

Abstract: Atherosclerosis is an inflammatory disease where lipopolysaccharide (LPS) triggers the release of inflammatory cytokines that accelerate its initiation and progression. Estrogen has been proven to be vasoprotective against atherosclerosis; however, the anti-inflammatory function of estrogen in the vascular system remains obscure. In this study, we investigated the effect of estrogen on LPS-induced monocyte chemoattractant protein-1 (MCP-1; listed as CCL2 in the MGI database) production in vascular smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 65 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Additionally, Nakagami et al (2010) have recently demonstrated that E 2 inhibits lipoprotein-a (an atherogenic lipoprotein)-induced expression of VCAM-1, ICAM-1 and E-selectin in bovine aortic endothelial cells and that IL1b, TNFa and MCP1 in macrophages differentiated from the THP-1 monocyte cell line. Indeed, E 2 inhibits MCP1 expression in rat thoracic aorta VSMCs (Jiang et al 2010) and inhibits human monocyte migration towards MCP1 in the culture, an effect that was abolished by ER blockade (Yamada et al 1996). The inhibition of monocyte migration was not demonstrated with testosterone treatment, suggesting that the ER effects are independent of testosterone conversion (Yamada et al 1996).…”
Section: Potential Signalling Mechanisms Of Testosterone In Vascular mentioning
confidence: 99%
“…Additionally, Nakagami et al (2010) have recently demonstrated that E 2 inhibits lipoprotein-a (an atherogenic lipoprotein)-induced expression of VCAM-1, ICAM-1 and E-selectin in bovine aortic endothelial cells and that IL1b, TNFa and MCP1 in macrophages differentiated from the THP-1 monocyte cell line. Indeed, E 2 inhibits MCP1 expression in rat thoracic aorta VSMCs (Jiang et al 2010) and inhibits human monocyte migration towards MCP1 in the culture, an effect that was abolished by ER blockade (Yamada et al 1996). The inhibition of monocyte migration was not demonstrated with testosterone treatment, suggesting that the ER effects are independent of testosterone conversion (Yamada et al 1996).…”
Section: Potential Signalling Mechanisms Of Testosterone In Vascular mentioning
confidence: 99%
“…LPS promotes inflammatory and immune responses via activation of almost all immune system cells, such as mac- rophages, mast cells, monocytes and VSMCs, which can cause over inflammation within atherosclerotic plaques. In VSMCs, LPS has been shown to induce the overexpression of many pro-inflammatory cytokines, including TNF-α, nitric oxide synthase, and MCP-1 [3,31,32] . Cur has been found to inhibit LPS-induced overexpression of vascular cell adhesion molecule-1 (VCAM-1), which plays a critical role in inflammatory responses within atherosclerotic plaques by regulating the [33] .…”
Section: Wwwchinapharcom Meng Z Et Almentioning
confidence: 99%
“…In addition, estrogens were demonstrated to reduce inflammatory activation of VSMC. For instance, the expression of COX2, MCP1, and endothelin 1 (ET1 (EDN1)) in response to serum, LPS, or Ang-II, respectively, was markedly attenuated in VSMC exposed to E 2 (Seli et al 2001, Hong et al 2004, Kawagoe et al 2007, Jiang et al 2010. Xing et al (2007) found that E 2 inhibits TNFa-stimulated expression of the neutrophil-specific chemokine cytokine-induced neutrophil chemoattractant (CINC)-2b and suggested that this effect might be responsible for the reduced infiltration of neutrophils, which is observed in animal models after vessel injury.…”
Section: Short Termmentioning
confidence: 99%